Doctor-patient relationship, leader-member exchange, occupational commitment, turnover intention: a study of public hospital doctors in China - Zeng Weilong (2019)
The strained doctor–patient relationship(DPR) negatively affects doctors’occupational commitment (OC) and turnover intention (TI), which affects the achievement of the goals of Healthy China 2030.Therefore,determining ways of improving DPRand doctors’OCand reducing TIis very important for achieving these goals. In the present study, two rounds of surveys were conducted among doctors at the Fourth Affiliated Hospital of Guangxi Medical University. Three hundred and eightyone valid questionnaires were collected over a period of three months, to explore the relationship between leader–member exchange (LMX), DPR, OC, and TI,using correlation analysis, variance analysis, exploratory and confirmatory factor analysis, and structural equation modeling (SEM)methods. The analysis results show that the China-specific doctor-based DPR scale has two dimensions with good validity and reliability. There is a significantly positive relationship among LMX, DPR and OC; they are all negatively correlated with TI. According to SEM, the impact paths of DPR between LMX and OC include: LMX→DPR (β＝0.35),DPR→OC (β＝0.73); the overall impact effect is 0.252;the impact paths of DPR between LMX and TI include: LMX→DPR, DPR→TI (β＝-0.25), LMX→TI (β＝-0.23); the overall impact effect is -0.317 and the mediating effect accounts for 27.76 percent of the overall effect. Research results reveal LMX positively correlates to DPR; DPR plays a partially mediating role between LMX and TI and a full mediating role between LMX and OC. This thesis offers suggestions for improving DPR and OC and reducing TI on management practice.